ANALISIS IMPLEMENTASI PENDEKATAN KONTEKSTUAL BERBASIS FENOMENA LINGKUNGAN SEKITAR PADA PEMBELAJARAN IPA DI SMP - Putri Izza Hilya Zahiy; Faiq Makhdum Noor (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to analyze the implementation of contextual teaching and learning (CTL) based on environmental phenomena across all science subjects at SMP Tahfidz Duta Aswaja Kudus. This research employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The sample was selected using purposive sampling. The results indicate differences in CTL steps between theory and classroom practice. In theory, CTL steps include: invitation, linking, constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. In practice, the steps include: presentation of phenomena, constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. Furthermore, there are differences between the theoretical and practical learning materials. In theory, the materials include: classification of living things, interactions of living things with the environment, environmental pollution, substances and their changes, energy and its transformations, force and motion, pressure, vibrations, waves and sound, human organ systems, electricity and magnetism, electromagnetism, the solar system, and biodiversity and environmental conservation. In practice, CTL is also applied to materials such as biotic and abiotic components, ecosystems, and Newton's laws. During CTL implementation, teachers face several challenges, including limited time, students’ lack of self-confidence, and teacher dominance in some lesson sessions. Nevertheless, students show positive responses, find it easier to understand the material, and actively participate in discussions and observations of phenomena. Overall, the contextual approach proves effective in creating meaningful learning and supporting the development of 21st-century skills.